PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KERJA PEGAWAI (Survei pada Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Karanganyar) - Riky Prasetya; Lamidi Lamidi; Edi Wibowo (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the significance of the influence of the work environment, work discipline and motivation on the performance of Karanganyar Regency's Office of Education and Culture. This study uses survey methods, the type of data used are qualitative and quantitative data, the source of the data used are primary data and secondary data. The population of this study were all 73 employees of the Karanganyar Regency Education and Culture Office. The sample was 73 people, so it is a census study. Methods of data collection using questionnaires and documentation. The data analysis technique used is validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. The results of the study concluded that there was a significant influence of the work environment on the performance of the Karanganyar Regency Education and Culture Department employees. There is a significant influence of Work Discipline on the performance of Karanganyar Regency Education and Culture Department employees. There is a significant influence of Motivation on the performance of the Karanganyar Regency Education and Culture Department employees.